Household consumption risk and coping strategies in Tajikistan: Evidence from household surveys - Enerelt Murakami (Asian Development Bank Institute (ADBI), 2017)
Forward-looking poverty analyses are essential for targeting and implementing poverty prevention interventions. In the presence of uncertainty and risk, the current poverty status of households is not a good indicator of whether they will be poor in the future. This paper examines consumption risk and risk-coping strategies in the case of Tajikistan, a country where frequent negative risks and adverse shocks are faced by its people. Our approach is to directly incorporate risk into the household welfare and poverty measures based on the financial concept of risk aversion and the volatility in welfare, measured by per-capita consumption. Using the derived measure of risk, we identify determinants of consumption risk and the use of coping strategies. The results show that higher risk and risk aversion is related to lower consumption and higher poverty. Household characteristics are important determinants of the consumption risk, while availability and accessibility of coping strategies are major factors for the choice of the coping strategies.
Keywords: I32; I38; I39; 330; consumption risk; poverty; coping strategies; Tajikistan